2022
DOI: 10.1039/d2ce00527a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of homogeneous (U,Am)O2 and (U,Pu,Am)O2 nanopowders

Abstract: Sinterable homogeneous nanoparticles of [U,(Pu),Am]O2 are produced hydrothermally from corresponding oxalates. The uranium and americium oxidation states are diverse in both as-synthesized nanopowders and sintered materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The main absorption maximum was set to 3890 eV for AmO 2 . 14 The maxima of the WLs are located at AmCl 6 3− (3888.4 eV), AmFe 2 (3887.5 eV) reported elsewhere. 15,16 Both Am M 5 edge data cited above were measured in conventional fluorescence mode and were similar to AmVO 3 and AmVO 4 (3888.5 eV) recorded in this work.…”
Section: Scanning Electron Microscopymentioning
confidence: 89%
“…The main absorption maximum was set to 3890 eV for AmO 2 . 14 The maxima of the WLs are located at AmCl 6 3− (3888.4 eV), AmFe 2 (3887.5 eV) reported elsewhere. 15,16 Both Am M 5 edge data cited above were measured in conventional fluorescence mode and were similar to AmVO 3 and AmVO 4 (3888.5 eV) recorded in this work.…”
Section: Scanning Electron Microscopymentioning
confidence: 89%
“…12 The process was reported for the rst time by Walter et al 11 and has already been applied in several studies. 12,15,28 In summary, the oxalates (U(C 2 O 4 ) 2 $6H 2 O and Np(C 2 O 4 ) 2 $6H 2 O), were directly precipitated from a U(IV) solution (0.47 M, obtained by electroreduction of a UO 2 (NO 3 ) 2 solution in 4 M HNO 3 with 0.5 M hydrazine) and from a Np(IV) solution (0.6 M in about 2 M HNO 3 ) with excess of 0.5 M oxalic acid. The oxalic acid dihydrate was supplied by Merck in analytical grade.…”
Section: Synthesismentioning
confidence: 99%
“…and their subsequent mobility have been highly reported in the literature. 6,[18][19][20] U(IV) also shows a strong Lewis acid behaviour depending on the pH conditions of the aqueous media which results in the hydrolysis properties according to eqn (1). 21 Intrinsic U(IV) colloids resulting from the condensation of the as-formed hydrolysed species represent another potential source of mobility for the radioactivity and should be taken into account to correctly estimate their behaviour in an environmental context (speciation, solubility, reactivity, redox, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…31 Recently, the approach allowed the group to successfully propose homogeneous NPs of mixed oxides (U,Pu)O 2 , (U,Am)O 2 and (U,Pu,Am)O 2 . 1,33 Also, the recent work of Tabata et al showed the formation of UO 2+x nanoparticles under hydrothermal treatment (100-450 °C) from U(IV) or U(VI) nitrates in the presence of organic additives (ethanol, aldehyde, carbonate, etc.). 34,35 The experimental conditions have an influence on the size, crystallinity and shape of the NPs, which can be spherical or rectangular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation